Radiative Effects on Mixed Convection in a Uniformly Heated Vertical Convergent Channel with an Unheated Moving Plate (Advances in Applied Mathematics and Mechanics, 2021)
Fluids engineering is extremely important in a wide variety of materials processingsystems, such as soldering, welding, extrusion of plastics and other polymericmaterials, Chemical Vapor Deposition (CVD), composite materials manufacturing.In particular, mixed convection due to moving surfaces is very important inthese applications. Mixed convection in a channel, as a result of buoyancyand motion of one of its walls has received little research attention and fewguidelines are available for choosing the best performing channel configuration,particularly when radiative effects are significant.In this study a numerical investigation of the effect of radiation onmixed convection in air due to the interaction between a buoyancy flowand an unheated moving plate induced flow in a uniformly heated convergentvertical channel is carried out. The moving plate has a constant velocityand moves in the buoyancy force direction. The principal walls of thechannel are heated at uniform heat flux. The numerical analysis isaccomplished by means of the commercial code Fluent. The effects ofthe wall emissivity, the minimum channel spacing, the converging angleand the moving plate velocity are investigated and results in terms ofair velocity and temperature fields inside the channel and wall temperatureprofiles, both of the moving and the heated plates, are given. Nusselt numbers,both accounting and not for the radiative contribution to heat removal,are also presented.